2001
DOI: 10.1046/j.1442-200x.2001.01329.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible effects of antioxidant status on increased platelet aggregation in childhood iron‐deficiency anemia

Abstract: Decreased antioxidant defense in IDA may cause increased oxidant stress, which, in turn, may result in a tendency towards platelet aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 18 publications
1
41
0
1
Order By: Relevance
“…In fact, patients with iron deficiency anemia who have no thrombocytosis can also be complicated by disturbance of retinochoroidal circulation. In addition, the functions of platelets such as aggregation activity can be altered in patients with iron deficiency anemia (13)(14)(15)(16). In the present case, almost normal prothrombin time (12.6 seconds) and activated partial thromboplastin time (26.2 seconds) were demonstrated at the time of diagnosis, suggesting that deregulation of the coagulation-fibrinolysis system was not mainly involved in the disturbance of retinochoroidal circulation.…”
Section: Discussionmentioning
confidence: 48%
“…In fact, patients with iron deficiency anemia who have no thrombocytosis can also be complicated by disturbance of retinochoroidal circulation. In addition, the functions of platelets such as aggregation activity can be altered in patients with iron deficiency anemia (13)(14)(15)(16). In the present case, almost normal prothrombin time (12.6 seconds) and activated partial thromboplastin time (26.2 seconds) were demonstrated at the time of diagnosis, suggesting that deregulation of the coagulation-fibrinolysis system was not mainly involved in the disturbance of retinochoroidal circulation.…”
Section: Discussionmentioning
confidence: 48%
“…Oxidant levels and antioxidant enzyme activities such as SOD, GSH-Px and CAT have been evaluated in several studies [8][9][10][11][12][13][14]. Although conflicting results have been reported [8,10], it is generally accepted that oxidative stress is increased through increase in oxidant levels and/or decrease in antioxidant enzyme capacities in IDA.…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative stress in IDA subjects was reported in several studies, in which the oxidative status was evaluated using measurement of oxidants, individual antioxidants, or both [8][9][10][11][12][13][14]. In these studies, it has been reported that oxidants were increased and antioxidants were decreased, and as a result, the oxidative/anti-oxidative balance shifted toward the oxidative side in patients with IDA.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bilic and Bilic have reported that the amino acid sequence homology of thrombopoietin and erythropoietin may explain the thrombocytosis in children with iron deficiency anemia [61]. In addition to the increased thrombotic risk associated with high platelet count, other possible mechanisms suggested is decrease in antioxidant defence in iron deficiency anemia leading to increased oxidant stress, which in turn may result in a tendency toward platelet aggregation [62]. Reduced deformability and increased viscosity of microcytic red blood cells in iron deficiency may be contributory by affecting blood flow patterns within the vessels [55].…”
Section: Ida and Thrombosismentioning
confidence: 99%